A university town and attraction/re-attraction of international students: an investigation into Dushu Lake higher education town in Suzhou, China. Issue 3 (3rd July 2021) - Kim, Hyung Min; Cocks, Matthew
ABSTRACT: While the attraction of international students makes a direct impact on the host city and the education institutions, retention (or reattraction) of them after their graduation can generate wider, indirect impacts on the local labor market. The link from international study to the labor market means the role of a gateway played out by the host city that offers university education and various urban attributes. This paper presents the relationship between international tertiary students, and the key factors for their attraction and re-attraction in the context of China. The case of the Dushu Lake Higher Education Town in Suzhou is investigated for how international students have interacted with the local built environment and whether this affects their plans to remain locally for work. This research found that the place based offer was generally less significant than the quality of academic institutions and economic prospects in attracting and re-attracting international students.